The impact of simultaneous correction of the V pattern on the results of surgical treatment in children with intermittent exotropia - Kochana, Malgorzata; Rosa, Agnieszka; Loba, Piotr (Graefe's archive for clinical and experimental ophthalmology, 2024)
Purpose This study is to investigate the impact of the coexistence of basic intermittent exotropia and vertical incomitance in the form of the V and sub-V pattern on the results of surgical correction of intermittent exotropia. Methods The records of 81 pediatric patients who had surgery for intermittent exotropia and a follow-up of more than 1 year were reviewed retrospectively. They were divided into groups: a concomitant group which underwent only horizontal muscle surgery of bilateral lateral rectus recession and a V pattern group which had additional inferior oblique recession, further separated into two subgroups: ≥ 15 prism diopters (classic V pattern group) and ≥ 10 < 15 prism diopters (sub-V pattern group). The surgical outcome, deviation control, stereoacuity, and postoperative drift were assessed after 3 months and 1 year postoperatively. Results Patients with sub-V and classic V pattern intermittent exotropia showed significantly better surgical success rate ( p = 0.025) and less postoperative drift ( p = 0.042) than patients without vertical incomitance. One year after surgery, successful surgical outcome was achieved in 83.72% of the vertically incomitant group: 80.76% for the classic V pattern and 88.24% for the sub-V pattern group, while only in 60.53% of nonpattern patients. Conclusions Patients operated for intermittent exotropia with a coexistent V pattern have consistently better surgical long-term results than those with only horizontal deviation. Additional inferior oblique recessions in the sub V pattern group provided excellent outcomes with no overcorrections; therefore, surgeons should consider addressing vertical incomitance even when the typical criteria for the V pattern are not met.